The IoT technologies acceptance in education by the students from the economic studies in Romania - Liliana Ionescu-Feleaga; Bogdan-Ștefan Ionescu; Mariana Bunea (Amfiteatru Economic Journal, 2021)
The main objective of this research is to test the IoT model of acceptance technologies (the Internet of Things) among the economics students from Romania. The Internet of Things refers to the interconnection between different devices via the Internet. Through this interconnection, the communication is no longer limited to the usual "human to human" form but is complemented by a new "object-to-object" form, which has a direct impact on the company's functions. In this context, the IoT technologies acceptance by the future economists and managers is extremely important. The study included 1,179 students from four university centers from Romania and the included factors from the acceptance of IoT technologies model (Internet of Things) were analyzed using the quantitative statistical methods in SPSS, applying a series of tests processed to highlight the research results, respectively the reliability test, the validity test, the chi-square test and the Person's correlation coefficient. The results of the study show the existence of a positive correlation between the research variables and indicate that the students from the economic studies, are ready to accept the new technological advances in IoT and to implement them in their future jobs.
Keywords: I23; I21; L86; M20; 330; Internet of Things (IoT); education; technology acceptance model; perceived utility; ease of use; intent to use; Romania